The 2018 outburst of BHXB H1743−322 as seen with MeerKAT. (11th October 2019) - Williams, D R A; Motta, S E; Fender, R; Bright, J; Heywood, I; Tremou, E; Woudt, P; Buckley, D A H; Corbel, S; Coriat, M; Joseph, T; Rhodes, L; et al.
ABSTRACT: In recent years, the black hole candidate X-ray binary system H1743−322 has undergone outbursts and it has been observed with X-ray and radio telescopes. We present 1.3 GHz MeerKAT radio data from the ThunderKAT Large Survey Project on radio transients for the 2018 outburst of H1743−322. We obtain seven detections from a weekly monitoring programme and use publicly available Swift X-ray Telescope and Monitor of All-sky X-ray Image data to investigate the radio/X-ray correlation of H1743−322 for this outburst. We compare the 2018 outburst with those reported in the literature for this system and find that the X-ray outburst reported is similar to previously reported 'hard-only' outbursts. As in previous outbursts, H1743−322 follows the 'radio-quiet' correlation in the radio/X-ray plane for black hole X-ray binaries, and the radio spectral index throughout the outburst is consistent with the 'radio-quiet' population.